Dual Liquid Junction Photoelectrochemistry: Part I. Dual-Cuvette and Dual-Thin-Film Cells for Screening and Quantification of Back-Contact Properties. Issue 12 (30th August 2017) - Kalan, Roghi E.; Russell, Margaret A.; Taylor, Jessica L.; Grimm, Ronald L.
Abstract : We explore methods for utilizing electrochemical redox contacts both at the front and back of illuminated semiconductors. A dual cuvette cell utilizes a cuvette/gasket/semiconductor/gasket/cuvette sandwich with rapid stirring and the capability for four-electrode measurements. Results from the dual-cuvette cell include current density–potential ( J – E ) scans with a cobaltocene +/0 back contact to n–Si(111) and a ferrocene +/0 front contact facing the illumination source, and a logarithmic plot of short-circuit current density vs open-circuit photovoltage for several illumination intensities to quantify the diode ideality factor for this cell. An ITO/liquid/semiconductor/liquid/ITO sandwich in a two-electrode configuration comprises a thin-layer cell. Thin-layer cell results include J – E scans as well as electrochemical impedance/Mott-Schottky analysis of flatband potentials. Results on n–Si(111) electrodes with two liquid junction contacts resemble results from traditional photoelectrochemical cells with a rectifying liquid-junction front contact and a rear metal contact.